Impact of the model of long‐term follow‐up care on adherence to guideline‐recommended surveillance among survivors of adolescent and young adult cancers. (15th June 2021) - Kagramanov, Dalia; Sutradhar, Rinku; Lau, Cindy; Yao, Zhan; Pole, Jason D.; Baxter, Nancy N.; Gupta, Sumit; Nathan, Paul C.
Abstract: Purpose: Adolescent and young adult cancer survivors require lifelong healthcare to address the late effects of therapy. We examined the impact of different provider models of long‐term follow‐up (LTFU) care on adherence to recommended surveillance. Methods: We conducted a retrospective cohort study using administrative health databases in Ontario, Canada. Five‐year survivors were identified from IMPACT, a database of patients aged 15–20.9 years at diagnosis of six cancers between 1992 and 2010. We defined three models of LTFU care hierarchically: specialized survivor clinics (SCCs), general cancer clinics (GCCs), and family physician (FP). We assessed adherence to the Children's Oncology Group surveillance guidelines for cardiomyopathy and breast cancer. Multistate models assessed adherence transitions and impacts of LTFU attendance. Results: A total of 1574 survivors were followed for a mean of 9.2 years (range 4.3–13.9 years) from index (5‐year survival). The highest level of LTFU attended in the first 2‐years post‐index was a GCC (47%); only 16.7% attended a SCC. By the end of study, 72% no longer attended any of the models of care and only 2% still attended an SCC. Among 188 survivors requiring breast cancer surveillance, 6.9% were adherent to their first required surveillance testing. Attendance at a SCC in the previous year and higher cumulative FP or GCC visits increased the rate of subsequently becoming adherent. Among 857 survivors requiring cardiomyopathy surveillance, 11% were adherent at study entry. Each subsequent SCC visit led to an 11.3% (95% CI: 1.05–1.18) increase in the rate of becoming adherent. Conclusion: LTFU attendance and surveillance adherence are sub‐optimal. SCC follow‐up is associated with greater adherence, but few survivors receive such care, and this proportion diminished over time. Interventions are needed to improve LTFU attendance and promote surveillance adherence. Abstract : Long‐term follow‐up care attendance and surveillance adherence are sub‐optimal among adolescent and young adult cancer survivors. Specialized survivor clinic follow‐up is associated with greater adherence, but few survivors receive such care, and this proportion diminished over time. Interventions are needed to improve the long‐term follow‐up care attendance and promote surveillance adherence.